Optimasi Waktu Kerja pada Proses Turning Body Valve di PT. X - Abdurrohman, Hanif Ilham; Syaifullah, Hafid (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
This study aims to analyze work time measurement in the turning process of body valves at PT. X using the Stopwatch Time Study method. The turning process of body valves is a critical stage in the production of valve components that affects the efficiency and quality of the final product. This research measures cycle time, normal time, and standard time, as well as identifies potential time wastage in the production process. The methods used include three types of processes: manual turning, CNC turning stage 1, and CNC turning stage 2, for body valves of three different sizes, A, B, and C. The results show that the standard time for sizes A, B, and C are 289.83 seconds, 416.46 seconds, and 757.27 seconds, respectively. The standard output generated is 0.00345 units/second for size A, 0.00241 units/second for size B, and 0.00132 units/second for size C. Based on this analysis, recommendations are provided for the optimization of resource allocation and production process improvement. By implementing accurate standard times, PT. X can increase efficiency, reduce waste, and strengthen its competitiveness in the market. This study is expected to serve as a reference for improving productivity and work quality in similar industries. Keywords: Productivity, Standard Time, Stopwatch Time Study, Time Measurement